Mechanical and flammability properties of hybrid recycled newspaper/ montmorillonite polypropylene composites - Zabidi, Mohd. Saiful Affendi (2013)
The objectives of this study are to study the effect of recycled newspaper (RNP) and ammonium polyphosphate (APP) content on mechanical properties and flammability properties of polypropylene (PP) and to determine the effect of APP content on mechanical and flammability properties of PP. In this research, RNP was gathered by collecting unused newspaper and was shredded it into small pieces. Then, it was soaked with NaOH solution (10 wt %) for 24 hours at room temperature. After that, it was rinsed with distilled water for several times. Montmorilloinite (MMT) was used as the other filler in PP. PP composites containing RNP were prepared by melt compounding using twin screw extruder followed by compression molding. The mechanical properties of PP composites were studied through tensile, flexural and impact tests. Limiting oxygen index test was used to investigate flammability properties of PP composites. Tensile strength reduced when RNP content increased while in APP content scope, it remains constant. Tensile modulus increased when RNP content increased and it remains almost constant when in APP content. Elongation at break reduced when RNP content increased while in APP content, it has no significant effects on it. Flexural strength increased when RNP content increased. Flexural strength reduced when APP content increased. Flexural modulus increased when RNP content increased and it remains constant when APP content increased. Impact strength increased when RNP content increased and it reduced when APP content increased. LOI value increased when RNP and APP content increased. From the first batch result, 20 wt% of RNP content formulation was used to produce second batch based on tensile strength and LOI value.